Cork industry waste product valorisation : bioactivity on human keratinocytes - Salvador, Maria Inês Vaz (2022)
Wound healing, a complex process that involves hemostasis, inflammation, proliferation and tissue remodelling, gathers deep scientific interest, since acute and chronic wounds are common as well as pathologic under or overhealing. Cork powder is one of the major waste derived residues in the cork industry, known to possess a strong phenolic content. We herein hypothesized that the products obtained from the cork liquefaction process may have biomedical properties particularly in the wound healing process. In this context, the aim of this work was to investigate the effect of several extracts obtained by manipulation of liquefied cork upon keratinocyte viability, migration and proliferation, key cellular events in the wound healing process. To do this, liquefied (LIQ) cork was produced and it was fractionated in water soluble (WS) and organic (ORG) extracts. Additionally, a glue dispersion (GLUE) was prepared by the addiction of WS extract to distilled water, Desmodur DA-L and cork powder on a ratio of 3:20:1.2:0.2. Several dilutions of each fraction were prepared (1:1, 1:5, 1:10, 1:100 and 1:1000) and used in 24-h treatment of the human keratinocyte HaCat cell line, for viability (MTT and LDH assays), migration capacity (wound-healing assay) and proliferation (BrdU assay) assessment. Additionally, total phenolic content (FolinCiocalteu method), and antioxidant potential (FRAP and DPPH) of each fraction were assessed. The liquefaction cork process achieved a biomass conversion of 94 %. Except for the highest concentration of ORG extract, the fractions were not cytotoxic and GLUE extract increased cell survival. All the cork extracts were able to induce cell proliferation and except for the GLUE fraction, they also induced cell migration capacity. Regarding antioxidant properties, ORG fraction showed the highest reducing power and radical scavenging activity, although LIQ fraction was the richest in phenolic content. On the other hand, GLUE fraction had the lowest phenolic content and accordingly, the lowest reducing power and radical scavenging activity. In conclusion, liquefied cork and its subproducts reveal wound healing-promoting bioactivity. Overall, WS extract produced the most consistent cellular responses, being thus the most promising for a potential biomedical application in wound healing. Nevertheless, further studies are recommended, mainly in vivo tests, to validate these in vitro results.